A Novel Reconfigurable Gate-Biasing Technique for Extending Dynamic Range in CMOS RF-DC Rectifiers Targeting RFEH Applications - Yi Joe Low; Yi Chen Lee; Wen Xun Lian; Harikrishnan Ramiah (Chips, 2025)
This paper presents a novel fully integrated radio frequency (RF) rectifier tailored for a wide power dynamic range (PDR) with multiband adaptability to efficiently convert AC RF power into DC power. The proposed rectifier utilizes the strength of interstage gate biasing to achieve high power conversion efficiency (PCE) across a broad range of input power levels. Through its reconfigurable mode, the circuit seamlessly transitions between a low-power path and high-power path to ensure optimal performance across a wide PDR. Simulated using CMOS 65 nm technology, the post-layout assessment reveals a peak PCE of 48.8% at 900 MHz and 46.4% at 1800 MHz, with an extensive PDR of 20 dB for PCE exceeding 20% at both frequencies.